The electoral photograph reloaded: a social semiotic approach - Veloso, Francisco Osvanilson Dourado (Letras, 2016)
While studies on the role of social media in political campaigns are growing, we still need to understand how well established communicative resources such as political photographs have been adapted in face of the digital transformation. Departing from Barthes (1972) discussion on electoral photographs, this paper discusses the production of Interactive meanings in photographs uploaded by the three main contenders in the Presidential Election 2014 in Brazil. The results show an expansion both in the functions and semiotic strategies adopted to establish a relationship with viewers through electoral photographs.